Analysis of The Relationship of Wind Speed and Rainfall on the Development of Coffee Leaf Rust (Hemileia Vastatrix B. & Br.) on Sipirok Arabica Coffee Plants in South Tapanuli District, Indonesia - Guntoro, Guntoro; Lisnawita, Lisnawita; Tantawi, A. Rafiqi; Safni, Irda (GMPI Conference Series, 2024)
Coffee is one of the agricultural commodities that is a priority for development by the Indonesian government because it has high economic value. Sipirok coffee is a mainstay Arabica coffee from the Highlands, South Tapanuli dictrict, Sumatera Utara - Indonesia. During its cultivation in the field, many problems were discovered, including coffee leaf rust disease caused by the fungus Hemileia vastatrix. This research aims to analysis the relationship between wind speed and rainfall on the development of coffee leaf rust disease (H.vastatrix) on Arabica coffee plants in South Tapanuli Regency, North Sumatere Province. The research was carried out at the community coffee planting center in the Sipirok Highlands, in Sampean Village, Sipirok District, South Tapanuli Regency with coordinates 1.64'N99.26'E with an altitude of 900 meters above sea level. The research was carried out by observing weather elements with a portable weather measuring device, capturing H. vastatrix fungal spores with a modified Kyosawa type spore capture device, and observing the severity of H. vastatrix coffee leaf rust disease. The collected data was analysed using correlation and regression analysis with SPSS Version 25. The results showed that wind speed and rainfall had a very positive effect on conidium capture and disease severity. Accordingly, there is a relationship between the elements of wind speed and rainfall on the development of coffee leaf rust disease (Hemileia broadatrix B. Br.).